Building a Rubric for Peer Review of Manuscripts in Psychological and Behavioral Sciences - Zaza, Haidar (Dirasat: Educational Sciences, 2021)
The purpose of this research is to build a rubric that can be used in peer review of research manuscripts in educational and psychological sciences. This rubric is built according to the Helvoort model for performance tasks, and its validity in the construction phase was confirmed by opinions of referees and its reliability was calculated by interrater reliability. The results of the construction stages showed the consensus of studies, methodologies in educational and psychological sciences and review forms used in journals on (6) criteria, namely: introduction, methodology, results, discussion, conclusions and recommendations, references and documentation. The results of the evaluation of rubric by judgments showed the comprehensiveness of its criteria and its relevance to the assessment of manuscripts, assisting the reviewers in focusing on research components, shortening review time, and achieving interrater reliability. It makes the beneficiaries (editor, reviewer, and author) trust its effectiveness and use it in review. Although the rubric is based on best practices in reviewing research manuscripts in educational and psychological sciences, it may not be generalized to other fields. It also provides a general and important vision that should be discussed further in the future.